EFEKTIVITAS REDUKSI GAS METANA (CH4) LIMBAH POME KELAPA SAWIT DENGAN METODE CONTINUOUSLY STIRRED TANK REACTOR (CSTR) DAN EFFLUENT POND - Sugiyatno Sugiyatno; Bintal Amin; Sofia Anita (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2025)
Palm oil plantations are a significant sector in Indonesia’s economy, with crude palm oil (CPO) production reaching over 43 million tons in 2020. However, this increased production also generates large amounts of liquid waste known as Palm Oil Mill Effluent (POME). POME contains high concentrations of organic substances that can pollute the environment and serve as a source of greenhouse gas emissions, particularly methane (CH₄), which has a global warming potential 25 times greater than carbon dioxide (CO₂). This study aims to evaluate the existing conditions of liquid waste treatment in the effluent pond system, examine the effect of mixing variations on methane production in the Continuously Stirred Tank Reactor (CSTR) system, compare the methane emission reduction efficiency between the two systems, and analyze the social and economic impacts of implementing these waste treatment technologies. The research was conducted at the Sei Pagar Palm Oil Mill owned by Perkebunan Nusantara V in Kampar Regency, Riau Province (coordinates N 00°19’35”, E 101°21’9”), from July to September 2023. The method used was quantitative experimental, involving sampling of liquid waste (POME) analyzed through both CSTR and effluent pond systems. Methane reduction was measured using a Biogas 5000 Analyzer, with supporting data obtained from relevant literature. The results indicate that sludge mixing duration has a significant effect on methane (CH₄) production. A mixing duration of 5 hours with a pump capacity of 20 m³/hour resulted in oil content in the reactor between 0.03% and 0.06% and higher methane production compared to mixing durations of 2, 3, and 4 hours. The CSTR system also demonstrated higher methane production efficiency than the effluent pond system, although optimal mixing still needs improvement. Waste treatment using CSTR technology positively contributes to reducing greenhouse gas emissions and provides economic and social benefits to the surrounding community. The implementation of this technology is recommended as a sustainable strategy to mitigate the negative impacts of the palm oil industry while enhancing renewable energy value